SCENARIO OF QUALITY OF WORK LIFE OF HOSPITAL STAFF - Kumar, Ashish; Sinha, Manish Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary purpose of this research paper is to study the effect of Gender, Age, Marital status, Nature of Jobs, and Area on the quality of work-life concerning hospital staff. This study is quantitative and descriptive; a structured five-point Likert scale questionnaire was used for data collection. 100 samples were selected using a convenient sampling approach from 30-plus-bed hospitals in Prayagraj city. Various tests and techniques were employed for the analysis, such as Mean, Standard Deviation, Correlation, and Multiple Linear Regression. Cronbach's Alpha value was used to test the reliability of the questionnaire. The results of this study will assist hospital policymakers in the implementation of quality work-life interventions to enhance the professional lives of employees. The present paper is one of the few studies carried out in the hospital staff because most of the studies were related to nurses, medical professionals, and doctors. Minimal research was done in this area related to hospital staff (non-medicos) taking as a whole.